Pengaruh Perencanaan Strategis Dan Koordinasi Terhadap Efektivitas Kerja Pegawai Di Sekretariat Daerah Kabupaten Bogor - Yadi Supriyadi; Ana Chaerunisyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to analyze the influence of Transformational Leadership, Perceived Organizational Support, and Organizational Culture on Employee Performance, with Organizational Citizenship Behavior (OCB) as the mediating variable, at PT Dolphin. Increasingly intense business competition requires companies to improve employee performance through effective leadership, adequate organizational support, and a strong organizational culture. This study used a quantitative approach using a survey method. The study population consists of all employees at PT Dolphin, while the sampling technique used is saturation sampling (census), meaning that all members of the population were included as respondents. Data collection was conducted by distributing a questionnaire using a fivepoint Likert scale. Data analysis was performed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and the coefficient of determination (R²). The results indicate that Transformational Leadership, Perceived Organizational Support, and Organizational Culture have a positive and significant effect on Organizational Citizenship Behavior, both partially and simultaneously. Furthermore, Transformational Leadership, Perceived Organizational Support, Organizational Culture, and Organizational Citizenship Behavior also have a positive and significant effect on Employee Performance. The results of the mediation indicate that Organizational Citizenship Behavior significantly mediates the effects of Transformational Leadership, Perceived Organizational Support, and Organizational Culture on Employee Performance. The implications of this study provide recommendations to the management of PT Dolphin to continue developing a transformational leadership style, increase attention to employee well-being and support, and build a positive organizational culture to encourage Organizational Citizenship Behavior and sustainably improve employee performance. Keywords Transformational Leadership, Perceived Organizational Support, Organizational Culture, Organizational Citizenship Behavior, Employee Performance